Stability of neomycin resistance in Staphylococcus aureus - Ayliffe, G. A. J. (1970)
A strain of Staphylococcus aureus isolated from the skin of a subject with eczema showed a loss in resistance to neomycin and tetracycline after treatment with neomycin was stopped. Seven out of 22 strains of neomycin-resistant Staph. aureus showed a loss in resistance to neomycin and streptomycin after storage in nutrient broth for 14 days at room temperature, and it seems probable that resistance in these unstable strains was controlled by extrachromosomal elements or plasmids. Strains of phage types 84/85 and 29/77 and related types were frequently isolated in general hospital wards and showed no loss in resistance on similar storage in nutrient broth. Five of the neomycin-unstable strains were isolated from patients with eczematous lesions. Multiple-resistant and antibiotic-sensitive strains of Staph. aureus of similar phage type were isolated from patients in a ward for patients with skin disease, and the possibility of transfer of resistance in vivo is discussed.